2023
DOI: 10.3390/met13071256
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Buckling Behavior and Strength of Combined Opening Plate Girders in Passenger Ships

Abstract: High-stiffener-web combined opening girders used on passenger ships are prone to plastic hinge failures around the opening area and overall instability under combined and vertical loads, exhibiting complex buckling behaviors. In response to such situations, a series of numerical simulations and experiments on combined opening girders were conducted, considering several affecting factors such as opening shapes, initial crack defects, strengthening measures and stiffener web dimensions. On the basis of the verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The specimen size for the tensile experiment was determined according to the Chinese national standard (GB-T 228.1-2021) [38]. In the previous experiments on the combined opening girders, it was found that the structure would fail in a complex manner such as instability and local buckling under the central vertical load applied from the plate [39]. Most of the existing plated grillage experiments focused on the failure behavior under longitudinal and transverse compressive loads, ignoring the effect of vertical bending loads from the plate [28,29].…”
Section: Simulation Settingsmentioning
confidence: 99%
“…The specimen size for the tensile experiment was determined according to the Chinese national standard (GB-T 228.1-2021) [38]. In the previous experiments on the combined opening girders, it was found that the structure would fail in a complex manner such as instability and local buckling under the central vertical load applied from the plate [39]. Most of the existing plated grillage experiments focused on the failure behavior under longitudinal and transverse compressive loads, ignoring the effect of vertical bending loads from the plate [28,29].…”
Section: Simulation Settingsmentioning
confidence: 99%
“…Chen et al [12] focused on analyzing the buckling behavior and strength of girders in passenger ships. Their study's originality lies in its comprehensive approach, combining experimental and numerical methods to evaluate the performance of girders with different opening shapes, initial crack defects, and strengthening measures.…”
Section: Radwan and Kovesdimentioning
confidence: 99%